Sinus augmentation and dental implant placement after breast cancer therapy- A case report - Mahmood, Maahin; Zia, Afaf; Andrabi, S. Mukhtar UN.; Fatma, Shazra; Ahmad, Mohammad; Jawed, Urfi (Journal of Case Reports in Dental Medicine, 2025)
IntroductionThis case report aims to provide implant-supported rehabilitation in a patient treated for breast cancer using sinus augmentation.MethodsA 57-year-old female patient previously treated for stage 2 breast-cancer with breast-conserving surgery, chemotherapy and radiotherapy presented with missing teeth in her upper right buccal segment and wanted its rehabilitation. Sinus augmentation with hydroxyapatite and ? tricalcium phosphate graft was performed to gain lost bone volume in the region using piezoelectric surgical unit. Final restoration was done using an implant-supported prosthesis.ResultsAfter sinus augmentation, implants were placed and successful osseointegration was observed with uneventful healing. The patient was satisfied with the final outcome of the treatment as proper oral form and function was achieved.ConclusionThis case report suggests that sinus augmentation using a piezoelectric unit followed by implant-supported prosthetic rehabilitation can provide successful outcomes if done cautiously in medically compromised patients.